Multivalued Variational Inequalities with -Pseudomonotone Mappings in Reflexive Banach Spaces - A. M. Saddeek; S. A. Ahmed (Abstract and Applied Analysis)
This paper is concerned with the study of a class of variational inequalities with multivalued -pseudomonotone mappings in reflexive Banach spaces by using the -antiresolvent technique. An application to the multivalued nonlinear -complementarity problem is also presented. The results coincide with the corresponding results announced by many others for the gradient state.